Identification of a unique membrane-bound molecule on a hemopoietic stem cell line and on multipotent progenitor cells. - Han, X D (1995)
Hemopoietic stem cells are a distinct population of cells that can differentiate into multilineages of hemopoietic cells and have long-term repopulation capability. A few membrane-bound molecules have been found to be preferentially, but not uniquely, present on the surface of these primitive cells. We report here the identification of a unique 105-kDa glycoprotein on the surface of hemopoietic stem cell line BL3. This molecule, recognized by the absorbed antiserum, is not present on the surface of myeloid progenitors 32D and FDC-P1 cells, EL4 T cells, and NIH 3T3 fibroblasts. This antiserum can also be used to block the proliferation of BL3 cells even in the presence of mitogen-stimulated spleen cell conditioned medium, which is known to have a stimulating activity on BL3 cells. It can also inhibit development of in vitro, fetal liver cell-derived multilineage colonies, but not other types of colonies, and of in vivo bone marrow cell-derived colony-forming unit spleen foci. These data suggest that gp105 plays an important role in hemopoietic stem cell differentiation.